MiR‐26a inhibits proliferation and motility in bladder cancer by targeting HMGA1. Issue 15 (22nd June 2013) - Lin, Yiwei; Chen, Hong; Hu, Zhenghui; Mao, Yeqing; Xu, Xianglai; Zhu, Yi; Xu, Xin; Wu, Jian; Li, Shiqi; Mao, Qiqi; Zheng, Xiangyi; Xie, Liping
Abstract : It is increasingly clear that microRNAs play a crucial role in tumorigenesis. Recently, emerging evidence suggested that miR‐26a is aberrantly expressed in tumor tissues. In our study, frequent down‐regulation of miR‐26a was observed in 10 human bladder cancer tissues. Forced expression of miR‐26a in the bladder cancer cell line T24 inhibited cell proliferation and impaired cell motility. High mobility group AT‐hook 1 (HMGA1), a gene that modulates cell cycle transition and cell motility, was verified as a novel target of miR‐26a in bladder cancer. These findings indicate an important role for miR‐26a in the molecular etiology of bladder cancer and implicate the potential application of miR‐26a in bladder cancer therapy. Abstract : miR‐26a is down‐regulated in bladder cancer tissue samples. miR‐26a inhibits bladder cancer cell T24 proliferation and motility. HMGA1 is a direct target of miR‐26a. HMGA1 is frequently over‐expressed in bladder cancer tissue. HMGA1 can promote T24 cell cycle progression.